2007
DOI: 10.1109/tbme.2007.900781
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Fibrillation Potentials—Analysis of Time Parameters in the Muscle Intracellular Action Potential

Abstract: A single fiber action potential (SFAP) can be modelled as the convolution of a biolectrical source and a filter impulse response. In the Dimitrov-Dimitrova (D-D) convolutional model, the first temporal derivative of the intracellular action potential (IAP) is used as the source, and Tspl is a time parameter related to the duration of the IAP waveform. This paper is centred on the relation between Tspl and the main spike duration (MSD), defined as the time interval between the first and third phases of the SFAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…The results of the present work suggest that we should admit some variability in the duration of the IAP depolarization portion in order to be able to generate the range of risetimes observed experimentally. This proposal is in agreement with several other studies that have demonstrated that to explain the changes of certain SFAP parameters it is necessary to consider the excitation source as a variable function (Rodriguez et al, 2006(Rodriguez et al, , 2007(Rodriguez et al, , 2009(Rodriguez et al, , 2010.…”
Section: Considerations For Future Sfap and Mup Modelingsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present work suggest that we should admit some variability in the duration of the IAP depolarization portion in order to be able to generate the range of risetimes observed experimentally. This proposal is in agreement with several other studies that have demonstrated that to explain the changes of certain SFAP parameters it is necessary to consider the excitation source as a variable function (Rodriguez et al, 2006(Rodriguez et al, , 2007(Rodriguez et al, , 2009(Rodriguez et al, , 2010.…”
Section: Considerations For Future Sfap and Mup Modelingsupporting
confidence: 91%
“…However, by making the same assumptions as we made for the rise-time, analysis of the (3). The ranges of variation of excitation and IR parameters have been chosen to be the same as or similar to those used in previous works (Nandedkar and Stålberg, 1983;Rodriguez et al, 2007;Arabadzhiev et al, 2008). …”
Section: Analysis Of the Factors Affecting Sfap V Ppmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameter A 2b has a variation of ± 0.5 around the value of A 2 . Parameter T spl ranges from 1.0 to 3.5 ms, in accordance with our previous studies (Rodríguez-Falces et al, 2006;Rodríguez-Falces et al, 2007).…”
Section: Default Values For the Excitation And Impulse Response Paramsupporting
confidence: 90%
“…A method for estimating the T spl value of an IAP from the MSD (time interval from the two SFAP positive peaks) of its SFAP (see Fig. 1c) is proposed in Rodríguez-Falces et al (2007).…”
Section: Introductionmentioning
confidence: 99%